Strategi Kepala Sekolah dalam Perencanaan Transformasi Digital di Sekolah Dasar - Harmawati Harmawati; Muchammad Eka Mahmud; Ahmad Muaddin (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Agama Islam Nahdlatul Wathan Samawa Sumbawa Besar, 2026)
Digital transformation in elementary education aims to improve the quality of learning, the effectiveness of school management, and student readiness to face the challenges of the 21st century. However, the implementation of digital transformation in elementary schools still faces various challenges, particularly related to infrastructure, teachers' digital literacy, and human resource readiness. The purpose of this study is to analyze the principal's strategy in planning digital transformation at SD Negeri 006 Palaran. The method used in this study is descriptive qualitative, with data collection conducted through interviews, observation, and documentation. The research findings indicate that the principal plays a crucial role as an agent of change through the formation of a Digital Task Force Team, the development of a digital transformation roadmap, the implementation of ongoing teacher training, and the development of a collaborative work culture that utilizes technology. The availability of digital facilities such as the internet, computers, and online learning platforms also supports the success of digital transformation.